2004
DOI: 10.1136/hrt.2002.007138
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcome up to 30 years after the Mustard or Senning operation: a nationwide multicentre study in Belgium

Abstract: Objective: To assess long term outcome of patients who underwent Mustard or Senning repair for transposition of the great arteries up to 30 years earlier.Design: Retrospective review of medical records.Setting: The six university hospitals in Belgium with paediatric cardiology departments.Patients: 339 patients were reviewed, of whom 124 underwent the Mustard procedure and 215 the Senning procedure. This represents almost the entire population of patients in Belgium with either simple or complex transposition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
150
1
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(176 citation statements)
references
References 15 publications
(18 reference statements)
14
150
1
8
Order By: Relevance
“…during exercise, a further increase in heart rate enables a further increase in cardiac output. However, our results, in concordance with other studies, show that d-TGA patients present with chronotropic incompetence 2,3,5,8 .…”
Section: Study Limitationssupporting
confidence: 82%
See 1 more Smart Citation
“…during exercise, a further increase in heart rate enables a further increase in cardiac output. However, our results, in concordance with other studies, show that d-TGA patients present with chronotropic incompetence 2,3,5,8 .…”
Section: Study Limitationssupporting
confidence: 82%
“…Nowadays, these atrial switch techniques are replaced by the arterial switch operation. However, 75% to 80% of the d-TGA patients have survived into adulthood and are still visiting the outpatient clinics for grown-up congenital heart disease 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Survival functional status and quality of life of patients with transposition of the great arteries (TGA), after an atrial switch operation (Senning or Mustard procedure) are reported to be reasonably good after 2 decades of life [1][2][3][4][5][6][7][8]. However, in many cases, It's possible to detect the function of the systemic right ventricle deteriorates, severe tricuspid regurgitation develops or the patients suffer from arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…Egy nemzeti belga tanulmányban a sajátunkhoz hasonló vizsgálatot mutattak be [19]. Ebben a közlemény-ben hat centrum eredményeit elemezték centrumonként hasonló betegszámmal.…”
Section: Megbeszélésunclassified
“…A nevezett vizsgálatban a két műtéti technika időben egyszerre került alkalmazásra szemben azzal, hogy egyetemünkön először csak Mustard-, majd csak Senning-műtéteket alkalmaztak. Hasonlóan eredményeinkhez, a két módszer mortalitási adatai nem különböztek, azonban a Senning-műtött betegek kedvezőbb funkcionális stádiumban voltak, nagyobb arányú volt a sportaktivitásuk és kevesebb volt a terelő-folttal kapcsolatos problémák aránya [19].…”
Section: Megbeszélésunclassified